الأبعاد الدلالية والتداولية للاستعارة الأيقونية دراسة سيميائية لسانية في الحديث النبوي الشريف - غصاب, منصور الصقر (قــــــراءات; No 08 (2015): (مجلة قراءات( مارس, 2019)
يهدف هذا البحث إلى دراسة الأبعاد الدلالية والتداولية للاستعارة الأيقونية في الحديث النبوي الشريف.  يكشف البحث عن أهمية الأنساق الاستعارية الأيقونية في تجسيد القضايا المجردة، أو الهيئات والصور، وتأليف العلاقات بين الدوال والمدلولات، والتعبير عن شيء غير مألوف، وتعميق الفكرة وتقويتها، وتوضيح المقاصد الدينية، وإيصال الترغيب والترهيب، والمدح والذم، ورصد مواضع القبح والجمال، وإبراز قواعد الدين في تشريعه وفقهه. الملخص باللغة الإنجليزية Semantic and Pragmatic function of the Iconic Metaphor Semiolinguistic Study in Al- Hadaith Al- Nabawy By Ghassab Mansoor Al- Saqr This study aims to examine the dimensions of Semanticals and Pragmaticals for Iconic Metaphor. Find reveal systems about the importance of metaphor in the iconic embodiment of abstract issues, or bodies and images, and the formation of relationships between functions and implications, and the expression of something unfamiliar, and deepen and strengthen the idea, and to clarify the religious purposes. Brought these systems carrot and the stick, and praise and slander, and spotted ugliness and beauty positions, highlighted the debt rules in the legislation and doctrine.